Journey into light: life and science of C. V. Raman - Venkataraman, G. (Banglore Indian Academic of Science, 1988)
C.V.Raman is best known to the scientific community for the effect which bears his name and other derivative terms, for which he won the Nobel Prize in Physics. This study of his life and work will benefit any reader with a serious interest in and concern for Indian science.
Keywords: Acoustics history; Physicists Biography India